Better and faster the proven path to unstoppable ideas - Gutsche, Jeremy 1978- (Crown Business, 2015)
In our world of chaos and change, what are you overlooking? If you knew the answer, you'd be a better innovator, better manager, and better investor. Become better by learning how to overcome three neurological traps that block successful people from realizing your full potential. Then, get faster by learning six patterns of opportunity ... Convergence, Divergence, Cyclicality, Redirection, Reduction and Acceleration. Each pattern is a repeatable shortcut that has created fortunes for ex-criminals, reclusive billionaires, disruptive CEOs and ordinary people who unexpectedly made it big
Includes bibliographical references and index
Keywords: Success in business; Creative ability in business; Entrepreneurship -- Case studies; Marketing; Opportunity; Fallstudiensammlung